Resistance of Chip Block Pallet from Teak Wood Particle against Decay Fungi and Subterranean Termites - Alessandro Geovani Damanik; Dede Hermawan; Sukma Surya Kusumah; Ikhsan Guswenrivo; Deni Zulfiana; Wida Banar Kusumaningrum; Lisman Suryanegara; Riska Surya Ningrum; Iman Hidayat (Jurnal Sylva Lestari, 2023)
Wood biomass such as sawdust, particles, and chip obtained wood industry can be used as raw material for chip block pallets (CBP). This study evaluated the resistance of chip block pallets made from teak-sawn waste and polyurethane adhesive against decay fungi (white-rot and brown-rot fungi) and subterranean termites. The CBPs with dimensions of 9 × 9 × 9 cm and a target density of 0.6 g/cm3 were cold pressed at 9.8 MPa for 4 h using several polyurethane concentrations and composition of particle sizes. The termite and decay resistance tests were conducted following JIS K 1571 2004. The results showed that CBP treated with different polyurethane concentrations and composition of particle sizes was resistant to subterranean termite attacks. However, the CBP manufactured were not resistant to white-rot and brown-rot fungi attacks, showing more than 3% mass loss percentage. Considering the efficiency of polyurethane use, the study suggested the best content for using polyurethane in the manufacture of CBP is 4.5% with a particle size composition of 50 (4-14 mesh): 50 (> 60 mesh). Keywords: Biodeterioration, chip block pallet, polyurethane, teak wood particles